The relationship between direct marketing initiatives and purchase intention within the South African cosmetic industry. - Fuller, Ashleigh (The IIE, 2022)
Due to such a fast pace and competitive business world around us, cosmetic brands nowadays have no choice but to engage with direct marketing initiatives in order to ‘stand out’ within the market. Without brands ‘standing out’, this could have a major impact on customer purchasing patterns. For this reason it is imperative for brand managers to understand and be aware of the effectiveness that direct marketing initiatives have on customer purchase intention and customers attitude towards the brand. The study aims to describe the relationship between direct marketing initiates used by cosmetic brands and customer purchase intentions. The research made use of quantitative survey questionnaires for the purpose of collecting objective data, reflecting respondents level of purchase intention and their attitude towards the brand. The use of descriptive statistics is deemed fit for the study as the data which is collected and analysed, enables the researcher to understand the relationship which exists between direct marketing and purchase intention, as well as it was inexpensive and a great deal of information was collected in a quick manner. The researcher found that there was a significant and positive relationship between direct marketing initiatives used by cosmetic brands and customers purchase intention and that there was a significant and positive relationship between direct marketing initiatives used by cosmetic brands and customers attitude towards the brand. This study expands on the existing body of knowledge by investigating and describing the relationship between direct marketing, customer purchase intention and attitude in the context of the South African cosmetic industry.
Keywords: Buying patterns; Customer behaviour; Direct marketing; Cosmetic industry